Efficacy and safety of atezolizumab in the treatment of urothelial carcinoma: a systematic review and meta-analysis - Jun Xie; Qiu-yu Mao; Jun-hao Chen; Hong-jin Shi; Pei-qin Zhan; Hai-feng Wang (World Journal of Surgical Oncology)
Abstract Background There is still controversy regarding the safety and efficacy of atezolizumab for the treatment of urothelial carcinoma (UC). This research aimed to extensively investigate the effectiveness and safety of atezolizumab as a therapy for UC. Methods A thorough literature review was conducted using databases including PubMed, Embase, the Cochrane Library, and Web of Science. The search included studies published from the inception of each database until May 24, 2024. The primary outcomes, progression-free survival (PFS) and overall survival (OS), were calculated using hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs). Results Ten randomized controlled trials (RCTs) totaling 4,148 participants were included in our analysis. Compared to UC patients who received a placebo, either alone or in combination with chemotherapy medications, aggregated data showed that patients with UC who received atezolizumab had significantly longer OS(HR = 0.88, 95% CI [0.83, 0.94], p < 0.0001). Three RCTs also provided data on PFS, showing that patients who received atezolizumab, either in addition to or instead of chemotherapy, had significantly longer PFS than those who received placebo with or without chemotherapy (HR = 0.85, 95% CI [0.76, 0.95], p = 0.004). Conclusions Atezolizumab has demonstrated significant improvements in OS and PFS among patients with UC, offering crucial insights for decision-making in UC immunotherapy. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails , identifier [CRD42024556757].